IMPLEMENTATION OF AMONG SYSTEM IN PANCASILA EDUCATION LEARNING AT SMA NEGERI 11 SEMARANG - Mahmud, Aditiya; Haryati, Titik; Dewi, Sutjiati Kumala (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
This research is entitled “Implementation of Among System in Pancasila Education Learning at SMA Negeri 11 Semarang” which examines how Pancasila education teachers apply the among system that has been initiated by Ki Hajar Dewantara in learning in class XI D2 SMA N 11 Semarang. Teachers who are referred to as pamong have the task of ensuring the learning of Pancasila education with asih, asah, and asuh, besides that the teacher must also apply the educational motto Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, Tut Wuri Handayani. The purpose of this study is to find out how the application of the among system by teachers in learning Pancasila education at SMA N 11 Semarang. In order for the purpose of this study to be achieved, researchers used a qualitative descriptive approach. Data collection using observation, documentation and interview methods. Data analysis of this research are, (1) data reduction, (2) data presentation, and (3) conclusion drawing/verification. This research shows that Pancasila education teachers have implemented the among system, besides that there are supporting factors and inhibiting factors in the application of the among system in class XI D2 SMA N 11 Semarang.